Chronic exposure to outdoor air pollution and lung function in adults. Issue 8 (8th April 2009) - Forbes, L J L; Kapetanakis, V; Rudnicka, A R; Cook, D G; Bush, T; Stedman, J R; Whincup, P H; Strachan, D P; Anderson, H R
Abstract : Background: The extent to which chronic exposure to outdoor air pollutants influences lung function in adults is unclear. The aim of this study was to measure the association between chronic exposure to outdoor air pollutants and adult lung function. Methods: The relationship between measures of lung function (forced expiratory volume in 1 s (FEV1 ) and FEV1 as a percentage of forced vital capacity (FVC)) and average exposure to particulate matter <10 μm in diameter, nitrogen dioxide, sulfur dioxide and ozone was examined in four representative cross-sectional surveys of the English population aged ⩾16 in 1995, 1996, 1997 and 2001. Year-specific estimates were pooled using fixed effects meta-analysis. Results: Greater exposure to particulate matter <10 μm in diameter, nitrogen dioxide and sulfur dioxide was associated with lower adult FEV1 . The size of the effect on population mean FEV1 was about 3% for particulate matter <10 μm, and 0.7% for nitrogen dioxide and sulfur dioxide, for a 10 μg/m 3 increase in pollutant concentration. The effects were most marked in men, older adults and ex-smokers. FEV1 was not associated with ozone concentration. No associations were found between the pollutants and FEV1 as a percentage of FVC. Conclusions: Chronic exposure to outdoor air pollution is associated with modestly reduced FEV1 in adults.